Female pattern hair loss-An update - Yasmeen Jabeen Bhat; Najam-; Insha Latif; Iffat Hassan (Wolters Kluwer Medknow Publications, 2020)
Female pattern hair loss (FPHL) is nonscarring progressive thinning of hair with gradual decrease in the number of hair, especially in the frontal, central, and parietal scalp, due to a process known as follicular miniaturization. The etiopathogenesis of FPHL is complex with multiple factors such as genetics, inflammation, hormones, and environment playing role in it. It usually manifests as slowly progressive hair thinning, mainly over the vertex and upper parietal scalp, the frontal hairline is often spared and the miniaturization is also not as severe as in men. A thorough history, clinical examination, hair loss evaluation tests, dermoscopy, and scalp biopsy can help in establishing the diagnosis. Various biochemical tests may be needed in patients with hyperandrogenism. The treatment includes medical and surgical modalities. Topical minoxidil is still considered the first line of treatment. Along with medical therapy, cosmetic camouflage may also be needed in some cases.